2014
DOI: 10.18632/oncotarget.2193
|View full text |Cite
|
Sign up to set email alerts
|

The small heat shock protein B8 (HSPB8) confers resistance to bortezomib by promoting autophagic removal of misfolded proteins in multiple myeloma cells

Abstract: Velcade is one of the inescapable drug to treat patient suffering from multiple myeloma (MM) and resistance to this drug represents a major drawback for patients. However, the mechanisms underlying velcade resistance remain incompletely understood. We derived several U266 MM cell clones that resist to velcade. U266-resistant cells were resistant to velcade-induced cell death but exhibited a similar sensitivity to various proapoptotic stimuli. Careful analysis of proteosomal subunits and proteasome enzymatic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 49 publications
2
45
1
Order By: Relevance
“…However, in recent years, the number of patients resistant to bortezomib is increasing. The mechanisms of drug resistance are complicated and autophagy is one of the causes . Thus, targeting autophagy to overcome the drug resistance is an available strategy in MM therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent years, the number of patients resistant to bortezomib is increasing. The mechanisms of drug resistance are complicated and autophagy is one of the causes . Thus, targeting autophagy to overcome the drug resistance is an available strategy in MM therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Among this abundant literature, we found of especial interest the works of (1) Arulanandam and colleagues (Ottawa Hospital Research Institute, Ottawa, Canada), who discovered that a transcriptional modulator operating downstream of vascular endothelial growth factor receptors (VEGFRs) 208,209 suppresses Type I interferon (IFN) responses, 210 hence sensitizing the tumor vasculature to infection by oncolytic viruses, 211 and found that microtubule-destabilizing agents commonly employed in the clinic (e.g., paclitaxel) 212,213 synergize with oncolytic virotherapy by disrupting the translation of Type I IFN-coding mRNAs and by exacerbating the demise of cancer cells provoked by the cytopathic effect; 214 (2) Nishio and collaborators (Baylor College of Medicine, Houston, TX, US), who reported that an oncolytic adenovirus genetically engineered to express interleukin-15 (IL-15) and chemokine (C-C motif) ligand 5 (CCL5, also known as RANTES) improved the therapeutic potential of adoptively transferred T cells expressing a chimeric antigen receptor (CAR) 215,216 [218][219][220][221][222] a means to boost the replication (and hence the efficacy) of an oncolytic HSV-1 strain; 223 (4) Parrish and co-authors (St James's University Hospital, Leeds, UK), who discovered that an oncolytic reovirus enhances the capacity of the FDA-approved CD20-targeting monoclonal antibody rituximab 224,225 to stimulate antibody-dependent cellular cytotoxicity; 226 , who discovered that autonomous parvoviruses are endowed with a rather advantageous feature for the development of novel oncolytic virotherapies, namely, they neither trigger nor inhibit Type I IFN responses in normal and malignant cells; 236 (11) Zloza and coauthors (Rush University Medical Center, Chicago, IL, US), who suggested that the downregulation of leukocyte immunoglobulin-like receptor, subfamily B (with TM and ITIM domains), member 1 (LILRB1, also known as ILT2) in peripheral blood mononuclear cells may constitute a reliable biomarker of therapeutic responses to oncolytic virotherapy in cancer patients; 237 (12) Liikanen and colleagues (University of Helsinki, Helsinki, Finland), who propose that the circulating levels of the damage-associated molecular pattern high mobility group box 1 (HMGB1) [238][239][240][241] at baseline may constitute a robust prognostic factor as well as a predictive indicator of disease control up...…”
Section: Preclinical and Translational Advancesmentioning
confidence: 99%
“…Other inhibitors of UPS components have also been shown to uniquely target cancerous cells (Fiskus et al, 2014;Li et al, 2013;Pulvino et al, 2012;Tsukamoto et al, 2008). Finally, the resistant, refractive and recurrent traits of cancer have inevitably resulted in the turnover of promising drugs like Bortezomib, due to the development of resistance in response to treatment (Hamouda et al, 2014). Consequently, finding new compounds that can target oncogenic pathways is crucial to establish effective cancer therapies.…”
Section: Introductionmentioning
confidence: 99%